9x+8y=6

Simple and best practice solution for 9x+8y=6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9x+8y=6 equation:


Simplifying
9x + 8y = 6

Solving
9x + 8y = 6

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-8y' to each side of the equation.
9x + 8y + -8y = 6 + -8y

Combine like terms: 8y + -8y = 0
9x + 0 = 6 + -8y
9x = 6 + -8y

Divide each side by '9'.
x = 0.6666666667 + -0.8888888889y

Simplifying
x = 0.6666666667 + -0.8888888889y

See similar equations:

| t-2=-1 | | 4x-7+3x=90 | | -4z-z= | | -2-6x=-38 | | 2x+21=9x-63 | | 6x+55=2x+27 | | 3(4x+5)=17x+12-5x+3 | | 6x+35+9x=15(x+2)-25 | | y+34=19 | | 3-9x=84 | | 5y+12-5=22 | | 2(-x+8)=24 | | 2x^2+162=0 | | 6(x+2)=2(3x+8)-4 | | 3x+4-5x-14=10 | | 7d-4d-4d-6=2d | | 11x+2=14x-10 | | 10y=40x+3xy | | 2(t-2)=6 | | 7x-y=(x) | | 0.5(x+2)-(3x+8)=1.6(x-2)+9 | | 3(7x+20Y)+7(-3x+6y)= | | y-37=-67 | | -21=n-10 | | 2(2x+5)=40 | | 3(x-5)=2(x+1)+x | | 5+9x=-13 | | -5.7-44.2=-8.3v | | -7y+3=8y+1 | | 3(7x+20Y)7(-3x+6y)= | | 4x+8-3x-10=-33 | | -6-2x-1=4x+8-6x-3 |

Equations solver categories